Induction of Bioactive Compound Composition from Marine Microalgae (Lyngbya sp.) by using Different Stress Condition - Nurul Farhana, Rosly; Rabeah Adawiyah, Abdul Razak; Palaniselvam, Kuppusamy; M. M., Yusoff; Natanamurugaraj, Govindan (Journal of Coastal Life Medicine, 2013)
Objective: To the effect of salinity stress on the production of microalgae (Lyngbya chlorophyll pigments in the growth medium. sp.) and Methods: Stress was investigated by using green algae strains Lyngbya sp. in response to change dbiifofaecretinvte s ctroemssp ocuonnddist iwonitsh loiukte a1n0y modification of cell growth and biomass production rate. The %-40% were analyzed. Results: During the stress condition, various biochemical and microbiological assays were emxopnreitsosreedd .t hTaht e3 0photochemical composition was evaluated by GC-MS studies. The studies including chloroph%y lhl icgohnetre nsta.l inity stress was suitable for high phytochemical production rate Conclusions: Our study indicates the wide range of salinity stress to enhance the growth on microalgae culture and enhance the production of major secondary metabolites